The Lord of the Rings the two towers ([s.l.] New Line Cinema)
The fellowship has broken, but the quest to destroy the one ring continues, Frodo and Sam must entrust their lives to Gollum if they are to find their way to Mordor. As Saruman's army approaches, the surviving members of the fellowship, along with people and creatures from Middle-earth, prepare for battle. The war of the Ring has begun.
VCD
Screenplay by Fran Walsh & Philippa Boyens & Peter Jackson; producers Barrie M. Osborne, Fran Walsch, Peter Jackson ; directed by Peter Jackson.
Elijah Wood, Ian McKellen, Liv Tyler, Viggo Mortensen, Sean Astin, Cate Blanchett, John Rnys-Davies, Bernard Hill, Billy Boyd
Keywords: Baggins, Frodo (fictitious character)--Fiction.; Middle Earth (Imaginary Place)--Fiction.